Associations of alcohol consumption and dietary behaviors with severe cognitive impairment among Chinese older men and women. (4th March 2023) - Lee, Yen-Han; Bhurosy, Trishnee; Chang, Yen-Chang; Liu, Ching-Ti; Shelley, Mack
ABSTRACT: Background: China is a country with a large alcohol user population, but it also faces other public health challenges like the growth of older adult population and shift in dietary behaviors in the past few decades. We examined the associations of alcohol consumption and dietary behaviors with severe cognitive impairment among Chinese older men and women. Methods: We used panel data from three waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) to examine this topic of interest. Older adults who answered three survey waves were analyzed (age ≥ 65), with a total of 7, 950 observations (n = 7, 950). Results: In the panel logistic regression models, only former alcohol use was positively associated with severe cognitive impairment among older men (p < .05), but not in older women. Neither current light nor heavy alcohol consumption was associated with cognitive impairment. Older men and women who did not consume or rarely consume fruits and vegetables were more likely to develop severe cognitive impairment (all p < .01). Conclusion: Public health practitioners can use the empirical results from this research to identify what patterns of alcohol use and dietary behaviors can help prevent cognitive impairment among older adults.